2022
DOI: 10.21203/rs.3.rs-1514870/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Targeting the Post-Synaptic Proteome in Alzheimer Disease with Psychosis

Abstract: Individuals with Alzheimer Disease with psychotic symptoms (AD + P) experience more rapid cognitive and functional decline, and have reduced indices of synaptic integrity, relative to those without psychosis (AD-P). We hypothesized the postsynaptic density (PSD) proteome is altered in AD + P relative to AD-P, and that this proteomic signature could be used to nominate novel pharmacotherapies. Liquid-Chromatography/Mass Spectrometry analysis of PSDs from dorsolateral prefrontal cortex of AD + P, AD-P and cognit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… 27 A recent study reported that patients with AD+P had reduced postsynaptic density (PSD) proteins compared to patients with AD–P, so we used the only proteome data for AD+P in this study for more accurate results. 28 The PSD proteome was used to build the AD+P network. This proteomic signature was generated by Dr. Sweet's team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 A recent study reported that patients with AD+P had reduced postsynaptic density (PSD) proteins compared to patients with AD–P, so we used the only proteome data for AD+P in this study for more accurate results. 28 The PSD proteome was used to build the AD+P network. This proteomic signature was generated by Dr. Sweet's team.…”
Section: Methodsmentioning
confidence: 99%
“…Given that synapse loss is the main neuropathologic indicator of cognitive decline in AD, it has been postulated that the susceptibility to AD+P results from more synaptic impairment in AD+P compared to AD-P. 27 A recent study reported that patients with AD+P had reduced postsynaptic density (PSD) proteins compared to patients with AD-P, so we used the only proteome data for AD+P in this study for more accurate results. 28 The PSD proteome was used to build the AD+P network. This proteomic signature was generated by Dr. Sweet's team.…”
Section: Prediction Of Synergetic Effect Among Antipsychotic-antidepr...mentioning
confidence: 99%
“…For the systems pharmacology study, the postsynaptic density (PSD) proteome was used to build the AD+P network. This proteomic signature was generated by Dr. Sweet's team 39 . Information about antipsychotics, antidepressants and their targets were extracted from DrugBank (https://www.drugbank.ca/) 40 .…”
Section: Prediction Of Synergetic Effect Among Antipsychotic-antidepr...mentioning
confidence: 99%